Evaluation of the Potential Sensitization of Chlorogenic Acid: A Meta-Analysis. (16th May 2013) - Lin, Mingbao; Gong, Wan; Chen, Qian; Sun, Lijuan; Wang, Yingchao; Fan, Xiaohui
Abstract : Chlorogenic acid (CGA) widely exists in many plants, which are used as medicinal substances in traditional Chinese medicine injectables (TCMIs) that have been widely applied in clinical treatments. However, it is still controversial whether CGA is responsible for TCMIs-related hypersensitivity. Several studies have been performed to evaluate its potential sensitization property, but the results were inconclusive. Therefore, the aim of this study was to evaluate its potential sensitization systematically using meta-analysis based on data extracted from literatures, searching databases of PubMed, EMBASE, ISI Web of Knowledge, CNKI, VIP, and CHINAINFO from January 1979 to October 2012, a total of 108 articles were retrieved by electronic search strategy, out of which 13 studies met the inclusion criteria. In ASA test, odds ratio of behavior changes was 4.33 (1.62, 11.60), showing significant changes after CGA treatment (P = 0.004 ). Serum IgG, serum histamine, PLN cellularity, and IgG1 AFCs were significantly enhanced after CGA treatment (P < 0.05 ). Totally, these results indicated that CGA could induce a positive reaction in potential sensitization, and intravenous administration of it might be a key factor for sensitization triggering, which could at least warrant more careful application of TCMIs containing CGA in clinical practices.